Booster vaccination using bivalent DS-5670a/b is safe and immunogenic against SARS-CoV-2 variants in children aged 5–11 years: a phase 2/3, randomized, active-controlled study - Suzuki, Rino; Suda, Miharu; Ishida, Katsuyasu; Furihata, Kei; Ota, Aisaku; Takahashi, Kaori; Sakakibara, Sachiko; Nakayama, Tetsuo; Takeshita, Fumihiko (Frontiers in Immunology, 2024)
Background DS-5670 is a messenger ribonucleic acid (mRNA) vaccine platform targeting the receptor-binding domain (RBD) of the spike protein derived from severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2). Booster vaccination against coronavirus disease 2019 (COVID-19) with monovalent DS-5670a (incorporating mRNA encoding the RBD from the original SARS-CoV-2 strain) or bivalent DS-5670a/b (original and omicron BA.4-5 RBD antigens) is effective and safe in adults. Data from a phase 2/3 active-controlled, non-inferiority, pediatric study evaluating a third booster dose of DS-5670a/b are reported here. Methods Children aged 5–11 years who had completed the two-dose primary vaccination series with monovalent BNT162b2 (original strain) at least 3 months prior to enrolment were randomly assigned to receive DS-5670a/b (20 µg of mRNA) or bivalent BNT1 62b2 (original/omicron BA.4-5; 10 µg of mRNA) on Day 1. The primary efficacy endpoint was blood neutralization geometric mean titer (GMT) against SARS-CoV-2 (omicron variant BA.5.2.1) and immune response rate (≥ 4-fold increase in post-vaccination circulating anti-SARS-CoV-2 neutralizing activity) on Day 29. Results Among evaluable participants (DS-5670a/b, n = 74; bivalent BNT162b2, n = 75), the adjusted GMT ratio of DS-5670a/b to bivalent BNT162b2 on Day 29 was 1.636 (95% CI, 1.221, 2.190). Immune response rates were ≥ 89% with both study vaccines; adjusted difference 2.6% (95% CI, –7.8, 13.8). The prespecified non-inferiority margins were exceeded, and the study met the primary endpoint. DS-5670a/b also demonstrated broad neutralization activity across recent omicron sublineages and no cases of COVID-19 between Days 8–29 post-administration were reported. There were no novel safety concerns in the pediatric population at data cut-off. Conclusions Bivalent DS-5670a/b was non-inferior to bivalent BNT162b2 in terms of immunogenicity, and had a manageable safety profile, when administered as a heterologous booster in children aged 5–11 years. Clinical trial registration https://jrct.niph.go.jp/, identifier jRCT2031220665